A study on working capital management in micro and small foundry companies in Divinópolis, MG (Research, Society and Development, 2018)
Working capital management plays an important role in the performance of companies. The lack of working capital and difficulties in the financial area are among the main causes of inefficiency in the management of living businesses and it is the reason for the closure of those that have been extinguished. Thus, the goalof this paper was to analyze the main factors that influence the administration of working capital in the micro and small industries of Divinópolis, MG. An exploratory and descriptive research was carried out, which approach was qualitative and quantitative. The data were collected through a questionnaire applied toninecompanies in the casting sector of Divinópolis. It was generally concluded that the lack of computerization of companies, their predominantly familial character, low level of education and lack of training in the area of finance of their managers are the main barriers to efficient management of working capital.